The prevalence of different human papillomavirus genotypes in lesions of the uterine cervix as a method in risk assessment of cervical cancer - Dittrich, Corneli (Department of Pathology, 2025)
Cervical cancer carries significant morbidity and mortality worldwide and presents a global health challenge. Despite longstanding screening programmes for precursor lesions, there remains a high incidence and prevalence of disease. Cervical cancer is caused by persistent infection with Human Papillomavirus (HPV), a sexually transmitted, oncogenic virus. There are more than 100 different HPV genotypes. Of these, studies have largely shown that the high- risk types 16 and 18 account for most cancers. However, with improved screening methods, other genotypes in particular HPV 31, are also emerging as significant. It is therefore important that there is an increase in National health education drives, opportunistic cervical screening and management programmes, particularly in low-income and middle-income countries (LMICs) where the bulk of cervical cancer cases and cancer-related deaths occur. The South African health system is disparate in that most women do not have access to adequate screening and that a small percentage of women with access to private healthcare are prone to over-screening. There is access to prophylactic vaccination, however, the only formal program available exists in the public setting, with vaccination against two oncogenic HPV genotypes, types 16 and 18. Given that other genotypes are emerging as significant causes of cancer across other settings globally, there is need for data on the prevalence of the different high-risk HPV genotypes in the South African population. Adequate data regarding prevalence of specific High-risk genotypes will also guide vaccination choices. Aim: To establish the prevalence of the different high-risk Human Papillomavirus genotypes in precursor and malignant lesions of the uterine cervix within a South African cohort. To compare our results to published data on prevalence of different HPV genotypes to South African statistics, Sub-Saharan African statistics and global statistics. Method: This was a cross-sectional, retrospective study using data from a pre-existing anonymised database that was created during the validation of the BD Viper as a new platform. There are two main arms to the study: Cytopathology and Histopathology. In both, the prevalence of the different high risk HPV genotypes will be established in different cohorts. The former in different screening groups and the latter on confirmed cases of malignancy. HPV genotyping is available on different platforms with different assays. For this study the focus is on PCR-based tests. Other methodologies such as linear array will be included in the literature review. Available PCR tests include the Cepheid Test on the GeneXpert platform, the Roche assay on the Cobas® platform and the BD OnclarityTM assay on the Viper system. The former two tests report HPV 16, 18 and a pool of ‘other' high risk genotypes on LBC samples. The latter offers extended genotyping, beyond 16 and 18 on LBC and formalin fixed paraffin embedded tissue samples (FFPE). This study therefore aims to report on the results from screening of the routine LBC samples for diagnostic co-tests performed on Roche Cobas® 6000 HPV Test used as a validation benchmark for the BD OnclarityTM HPV Assay. In addition, the study will include the analysis of the findings on the performance of the BD OnclarityTM HPV Assay on the genotyping of formalin fixed paraffin embedded tissue samples of proven cervical squamous cell carcinoma and adenocarcinoma for validation purposes of FFPE testing. Results: In the first group in the cytology arm of the study (NILM, ASCUS and LSIL) the three most prevalent high-risk genotypes for all LBC samples were HPV P2 (HPV types 56, 59 and 66) at 23%, P3 (HPV types 35, 39 and 68) accounting for 18% and type 31 at 14%. Among high-grade precursor lesions (HSIL and AGC) on cytology HPV 16 was the most frequently detected genotype, accounting for 33% of the total genotypes identified, followed by HPV P3 (HPV types 35/39/68) [17%], HPV 52 (11%), and HPV P1 (HPV types 33/58) [9%]. V The other high-risk genotypes in precursor lesions are HPV P3 (HPV types 35/39/68), HPV 52 and HPV P1 (HPV types 33/58), and in invasive carcinoma are HPV 18, HPV P3 (HPV types 35/39/68) and HPV 45. There were neither squamous cell carcinomas nor adenocarcinomas diagnosed on LBC and therefore no genotype analysis was performed. On the histopathology samples of squamous cell carcinoma HPV 16 was the most frequently detected genotype, accounting for approximately half (49%) of the genotypes identified, followed by HPV 18 (13%), HPV P3 (HPV types 35/39/68) [9%], and HPV 45 (9%). In cervical adenocarcinoma HPV 18 was the most frequently detected genotype, accounting for 50% of the total genotypes identified, followed by HPV 16 (23%), HPV 45 (14%), and HPV P3 (9%). An interesting finding was that of multiple HPV oncotypes detected in single cases. Conclusion: HPV 16 is the most common genotype in high-grade precursor lesions and invasive squamous cell carcinoma. HPV 18 is the most common genotype in invasive adenocarcinoma of the uterine cervix. The other high-risk genotypes in high-grade precursor lesions are HPV P3 (35/39/68), HPV 52 and HPV P1 (33/58), and in invasive carcinoma are HPV 18, HPV P3 (35/39/68) and HPV 45. For better comparison assays should match, as our pooled group results does not distinguish between individual oncotypes. Further studies and a South African meta-analysis are needed. We recommend that for adequate vaccine prevention of carcinoma of the cervix, in addition to HPV 16 and HPV 18 more genotypes should be included i.e. vaccination with the nano valent vaccine which offers protection against high-risk HPV types 16, 18, 31, 33, 45, 52, and 58. As an added benefit vaccination with this vaccine also protects against genital warts (condyloma acuminata) caused by HPV types 6 and 11.